Oil Production in the Arctic National Wildlife Refuge: The Technology and the Alaskan Oil Context - United States. Congress. Office of Technology Assessment. (United States. Congress. Office of Technology Assessment., 1989)
This report presents the results of an assessment of a subset of these issues focusing in particular on: the oilfield technology being used to develop the Alaskan North Slope’s oil resources and the likely configuration of that technology as it might be applied in the future to the coastal plain; and the prospects for future North Slope oil production, especially the likelihood that the flow of oil through the Trans Alaskan Pipeline System will suffer a serious decline during the next decade.